2020
DOI: 10.1101/2020.04.01.019943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remdesivir inhibits renal fibrosis in obstructed kidneys

Abstract: Aim: Kidney impairment is observed in patients with . We aimed to demonstrate the effect of anti-COVID-19 agent remdesivir on renal fibrosis.Methods: Remdesivir and its active nucleoside metabolite GS-441524 were used to treat TGF-β stimulated renal fibroblasts (NRK-49F) and human renal epithelial cells (HK2). Cell viability was determined by CCK8 assay, and fibrotic markers were measured by Western blotting. Vehicle or remdesivir were given by intraperitoneal injection or renal injection through the left uret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…293 T cell line is derived from HEK293 cell line. It is very useful for various studies such as antiviral CRISPR ( Wang et al, 2020b ), virus isolation, ( Dai et al, 2020 ), MTHFD1 as a target of anti-viral therapy ( Xing et al, 2020 ), virus susceptibility ( Thevarajan et al, 2020 ), viral pathogenesis/transmission ( Gao et al, 2020 ), vaccine production ( Mantlo et al, 2020 ), immune response ( Ye et al, 2020 ; Ju et al, 2020 ), mAb production ( Li et al, 2020 ; Sun et al, 2020 ), mAbs screening ( Fintelman-Rodrigues et al, 2020 ), vaccine production and antibodies response ( Mossel et al, 2005 ), ACE-2 gene expression in target cells ( Zhang et al, 2020a ),for drug screening like Teicoplanin ( Wu et al, 2020 ). Similarly, 293 FT cell line is used for screening of DHODH Inhibitors ( Wang et al, 2020a ), MAbs production ( Li et al, 2020 ), and 293 F used for monoclonal antibodies production ( Li et al, 2020 ; Sun et al, 2020 ); whereas, 293 T-ACE-2 cell line for vaccine production and antibodies response ( Mossel et al, 2005 ) and viral pathogenesis ( Gao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…293 T cell line is derived from HEK293 cell line. It is very useful for various studies such as antiviral CRISPR ( Wang et al, 2020b ), virus isolation, ( Dai et al, 2020 ), MTHFD1 as a target of anti-viral therapy ( Xing et al, 2020 ), virus susceptibility ( Thevarajan et al, 2020 ), viral pathogenesis/transmission ( Gao et al, 2020 ), vaccine production ( Mantlo et al, 2020 ), immune response ( Ye et al, 2020 ; Ju et al, 2020 ), mAb production ( Li et al, 2020 ; Sun et al, 2020 ), mAbs screening ( Fintelman-Rodrigues et al, 2020 ), vaccine production and antibodies response ( Mossel et al, 2005 ), ACE-2 gene expression in target cells ( Zhang et al, 2020a ),for drug screening like Teicoplanin ( Wu et al, 2020 ). Similarly, 293 FT cell line is used for screening of DHODH Inhibitors ( Wang et al, 2020a ), MAbs production ( Li et al, 2020 ), and 293 F used for monoclonal antibodies production ( Li et al, 2020 ; Sun et al, 2020 ); whereas, 293 T-ACE-2 cell line for vaccine production and antibodies response ( Mossel et al, 2005 ) and viral pathogenesis ( Gao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other respiratory systems based In Vitro Model systems are A549 cell line for ACE2 gene expression ( Zhao et al, 2020b ), and for drug screening of ATAZANAVIR ( Ge et al, 2020 ), Teicoplanin ( Wu et al, 2020 ), DHODH inhibitors ( Wang et al, 2020a ); NCI-H1299 and BEAS-2B cell lines for viral pathogenesis and transmission cell line for vaccine production ( Mantlo et al, 2020 ); Primary culture of type II alveolar (AT2) cells for ACE2 gene expression ( Poschet et al, 2020 ); IB3-1 and its derivative S9 cells for the screening of Azithromycin and Ciprofloxacin ( Wang et al, 2020c ); and KMB17 cells for vaccine production ( Mantlo et al, 2020 ). Hep-2 cell line shown significant CoVs viral titer and have ACE2 receptor ( Hoffmann et al, 2020 ; Wang et al, 2020a ), and susceptible to SARS-CoV2; however, in another study, A549 cells did not show TMPRSS2 expression, required for S protein processing and viral spread ( Matsuyama et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were grown as previously described by our group [18]. Normal rat kidney interstitial fibroblasts (NRK-49F) rat kidney interstitial fibroblast cells were obtained from the National Infrastructure Cell Line Resource, Chinese Academy of Medical Sciences (cat.…”
Section: Cell Culturementioning
confidence: 99%
“…Pruijssers et al [142] reported that Remdesivir potently inhibits SARS-CoV-2 replication in human lung cells and primary human airway epithelial cultures (EC 50 = 0.01 µM), in Vero E6 cells (EC 50 = 1.65 µM), respectively. Wu et al [143] found that Remdesivir and GS-441524 can inhibit cell proliferation and the expression of fibrotic markers (fibronectin, pSmad3, and aSMA) in NRK-49F and HK2 cells. Brandi et al [144] used rhesus macaque model of COVID-19, and showed that Remdesivir can be used in transient lower respiratory tract disease.…”
Section: Biological Activity Of Remdesivirmentioning
confidence: 99%